Nepalese Null AMELY Males and their Y-Haplotypes - Jha, Dinesh K; Rijal, Jiwan Pd; Chhetri, Nirajan T (Scientific World, 2010)
Amelogenin is the well-liked process for sex typing in recent days. Exceptional failures to amplify AMELY accurate products can cause erroneous gender identification consequence male samples mistakenly identified as females. A total of 9 null AMELY males were noticed in 200 males of 72 Nepalese surnames by means of 4.5% frequency. No amplification of DYS458 Marker in all null AMELY males but great sharing of amplified Y STR alleles among them is a probable sign of the general phylogenetic origin. Key words: Forensic; Gender determination; Amelogenin; Null AMELY; Y-STR haplotypes etc. DOI: 10.3126/sw.v8i8.3858 Scientific World Vol.8(8) 2010 pp.97-101